A linear B-cell epitope close to the furin cleavage site within the S1 domain of SARS-CoV-2 Spike protein discriminates the humoral immune response of nucleic acid- and protein-based vaccine cohorts - Lorenz, Peter; Steinbeck, Felix; Mai, Franz; Reisinger, Emil C.; Müller-Hilke, Brigitte (Frontiers in Immunology, 2023)
Background Understanding the humoral immune response towards viral infection and vaccination is instrumental in developing therapeutic tools to fight and restrict the viral spread of global pandemics. Of particular interest are the specificity and breadth of antibody reactivity in order to pinpoint immune dominant epitopes that remain immutable in viral variants. Methods We used profiling with peptides derived from the Spike surface glycoprotein of SARS-CoV-2 to compare the antibody reactivity landscapes between patients and different vaccine cohorts. Initial screening was done with peptide microarrays while detailed results and validation data were obtained using peptide ELISA. Results Overall, antibody patterns turned out to be individually distinct. However, plasma samples of patients conspicuously recognized epitopes covering the fusion peptide region and the connector domain of Spike S2. Both regions are evolutionarily conserved and are targets of antibodies that were shown to inhibit viral infection. Among vaccinees, we discovered an invariant Spike region (amino acids 657-671) N-terminal to the furin cleavage site that elicited a significantly stronger antibody response in AZD1222- and BNT162b2- compared to NVX-CoV2373-vaccinees. Conclusions Understanding the exact function of antibodies recognizing amino acid region 657-671 of SARS-CoV-2 Spike glycoprotein and why nucleic acid-based vaccines elicit different responses from protein-based ones will be helpful for future vaccine design.